Optimized thin-film organic solar cell with enhanced efficiency - Farooq, W. (MDPI, 2021)
Modification of a cellâs architecture can enhance the performance parameters. This paper reports on the numerical modeling of a thin-film organic solar cell (OSC) featuring distributed Bragg reflector (DBR) pairs. The utilization of DBR pairs via the proposed method was found to be beneficial in terms of increasing the performance parameters. The extracted results showed that using DBR pairs helps capture the reflected light back into the active region by improving the photovoltaic parameters as compared to the structure without DBR pairs. Moreover, implementing three DBR pairs resulted in the best enhancement gain of 1.076 in power conversion efficiency. The measured results under a global AM of 1.5G were as follows: open circuit voltage (Voc) = 0.839 V; short circuit current density (Jsc) = 10.98 mA/cm2; fill factor (FF) = 78.39; efficiency (Î·) = 11.02. In addition, a thermal stability analysis of the proposed design was performed and we observed that high temperature resulted in a decrease in Î· from 11.02 to 10.70. Our demonstrated design may provide a pathway for the practical application of OSCs. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.